2005
DOI: 10.1080/08910600510044507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a cell preparation ofEnterococcus faecalisstrain EC-12 on digesta flow and recovery from constipation in a pig model and human subjects

Abstract: The effects of a cell preparation of Enterococcus faecalis strain EC-12 (EC-12) on the digesta flow in a pig model and its oral administration to humans were examined for its effect on frequency of defecation and faecal consistency. Latin square model was used in the pig study. Three sows fistulated at the caecum were fed a diet supplemented with either EC-12 or yeast cell wall (10 mg/kg body weight per day) for 9 days. An untreated control (C) was also obtained. Four markers (two were liquid and others solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…However, the relationship between probiotic lactobacilli and intestinal indigenous lactobacilli is very complex; we must consider not only bacterial ecology but also physiological responses of the intestine, such as absorption and secretion, digesta kinetics and retention time. Digesta kinetics is modified by fermented milk (23) and the cell component of LAB (27). The modification of digesta retention time should affect the bacterial composition, then the fermentation pattern (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between probiotic lactobacilli and intestinal indigenous lactobacilli is very complex; we must consider not only bacterial ecology but also physiological responses of the intestine, such as absorption and secretion, digesta kinetics and retention time. Digesta kinetics is modified by fermented milk (23) and the cell component of LAB (27). The modification of digesta retention time should affect the bacterial composition, then the fermentation pattern (28).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the lower dose levels (0.005% and 0.01%) of EC-12 did not prevent ED. Presently used EC-12 had a high cell pellet density of at least 5 trillion cells/g [15]. Therefore, the diet offered to pigs of E-0.05 group contained 2.5 × 10 9 E. faecalis EC-12 cells/g diet.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the NKCC1 gene was only achieved by a high dose of EC-12 which was 10-fold more concentrated than the normal dose. 5) Thus, the ability of EC-12 to induce inflammation or chloride secretion from IEC should be quite moderate compared to that of pathogens. This non-excess effect of EC-12 on chloride secretion from IEC could be beneficial for treating constipation because decreased chloride secretion activity is considered to be a cause of constipation.…”
Section: )mentioning
confidence: 99%
“…This non-excess effect of EC-12 on chloride secretion from IEC could be beneficial for treating constipation because decreased chloride secretion activity is considered to be a cause of constipation. 17) In fact, Tsukahara et al 5) have demonstrated in human subjects that the administration of EC-12 was effective for improving constipation. Considering that the human subjects took a normal dose of EC-12 for 30 days by Tsukahara et al, it is implied that long-term administration of EC-12 may stimulate NKCC1 expression even with a normal dose.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation